Altered biochemical parameters in the saliva of patients with breast cancer - YARAT, AYŞEN; AKBAY, TUĞBA (TOHOKU UNIV MEDICAL PRESS, 2008)
Saliva plays an important role in the protection of oral cavity and alterations in either salivary flow rate or protein composition may have dramatic effects on oral health. Prevention and management of oral complications of cancer and cancer therapy will improve oral function and quality of life, and reduce morbidity and the cost of care. The aim of this study was to investigate the saliva of patients with breast cancer biochemically and cytologically and compare with healthy controls. Accordingly, lipid peroxidation (LPO), total protein, salivary flow rate, and pH levels were measured in the saliva samples obtained from 20 breast cancer patients and I I healthy individuals. Tissue factor (TF) is a major regulator of normal hemostasis and thrombosis, and TF activity of saliva samples was evaluated. Under the conditions used, patients with breast cancer present a significant reduction in total protein, pH and LPO levels. Salivary TF activity was higher in breast cancer patients than that in control subjects, but the degree of increase was not statistically significant. In addition, the analysis of saliva samples by SDS polyacrylamide gel electrophoresis showed the retarded mobility of the 66-kDa proteins and the increased proteins of about 36 kDa in the patient group. Some patients with breast cancer had increased number of leucocytes. Importantly, dysplastic cells and yeast cells were detected only in saliva samples of cancer patients. Decreased salivary LPO may be considered as a risk factor for breast cancer.
Keywords: breast cancer; saliva; tissue factor; lipid peroxidation; protein; TISSUE FACTOR; BLOOD; PLASMA